Micro-pitting and wear assessment of engine oils operating under boundary lubrication conditions. (January 2019) - Vrcek, A.; Hultqvist, T.; Baubet, Y.; Björling, M.; Marklund, P.; Larsson, R.
Abstract: Current state-of-the-art engine oils tend to enhance micro-pitting damage in rolling contacts under certain operating conditions. ZDDP anti-wear additive was shown to promote such behavior. However, in order to optimize an engine oil formulation for rolling contacts, further studies are needed to assess engine oils in terms of micro-pitting and wear damage. This investigation studies the micro-pitting and wear performance of a number of engine oils for rolling contacts in a ball-on-disc configuration under conditions prevalent in crankshaft roller bearing applications. Based on the results it was concluded that an engine oil containing higher blend of PAO base oil compared to the oil mixture of Group III and PAO has a lower tendency towards micro-pitting and wear. Highlights: Engine oils were assessed based on micro-pitting and wear damages. Higher blend of PAO oil improves the tendency towards micro-pitting and wear. Lower additive concentration and lower viscosity reduce tendency towards micro-pitting but promote mild wear. Micro-pitting and mild wear are the competing mechanisms.